1995
DOI: 10.3109/01902149509031771
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Epidermal Growth Factor Receptor in Alveolar Epithelium During Human Fetal Lung Development in Vitro

Abstract: Epidermal growth factor (EGF) enhances alveolar type II cell differentiation. In human fetal lung explants, EGF stimulates surfactant protein A (SP-A) synthesis. This effect may occur through a direct interaction of the ligand on EGF receptors located within distal pulmonary epithelium during alveolar type II cell differentiation. To determine if EGF receptor is present in alveolar epithelium, immunostaining for EGF receptor and in situ hybridization for EGF receptor mRNA were performed in human fetal lung exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 40 publications
(22 reference statements)
1
9
0
Order By: Relevance
“…Previously, others have demonstrated that RA increased EGFRs in kidney epithelial cells (Kawaguchi et al 1994), fetal lung cell lines (Oberg et al 1988;Oberg and Carpenter 1991), and mouse fibroblast lines (Jetten 1980). The isolation of EGFRs from the membrane surface of the type II pneumocyte in the present study is consistent with the localization of the receptor in the alveolar epithelium as reported by others (Klein et al 1995;Rice et al 1999). While RA did increase expression of the EGFR in the ELISA at high cell density (1×10 5 cells/well), it inhibited thymidine incorporation at high cell density.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Previously, others have demonstrated that RA increased EGFRs in kidney epithelial cells (Kawaguchi et al 1994), fetal lung cell lines (Oberg et al 1988;Oberg and Carpenter 1991), and mouse fibroblast lines (Jetten 1980). The isolation of EGFRs from the membrane surface of the type II pneumocyte in the present study is consistent with the localization of the receptor in the alveolar epithelium as reported by others (Klein et al 1995;Rice et al 1999). While RA did increase expression of the EGFR in the ELISA at high cell density (1×10 5 cells/well), it inhibited thymidine incorporation at high cell density.…”
Section: Discussionsupporting
confidence: 94%
“…Alveolar cells express both EGF and EGFR proteins (Raaberg et al 1991;Raaberg et al 1992;Klein et al 1995). To our knowledge, no information is available on regulation of EGFRs by RA in adult type II pneumocytes.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, messenger RNA (mRNA) for both ligands is found in mesenchymal tissue from human fetal lung throughout gestation (17), observations suggestive of a paracrine effect of EGF/TGF-␣ on alveolar type II cell differentiation. EGF receptor protein and mRNA are found in alveolar epithelium from midtrimester human fetal lung explants that have undergone spontaneous differentiation in vitro (19). Thus, the presence of EGF receptor and its ligands in distal pulmonary epithelium during human fetal lung development suggests a regulatory role for EGF in type II cell differentiation.…”
mentioning
confidence: 96%
“…This process depends on interaction between epithelium and mesenchyme 32 as first described in 1976 33 and with further support provided by recent studies in transgenic mice. 34 The control of growth of airways and epithelium is mediated by extracellular matrix (ECM) molecules, 35,36 transcription factors, 5,32,[37][38][39] growth factors, [40][41][42][43][44][45] neuropeptides, [46][47][48][49] fetal lung liquid, 50,51 and mechanical stress elicited by respiratory movements. 52,53 However, the clinical significance of these factors and their interactions are still under study.…”
Section: Factors Controlling Growth Of Airways and Epitheliummentioning
confidence: 99%